Exploring the Shadows: Dark Tourism in India - Goyal, Jigisha; Gaurav, Kunal (International Journal of Engineering and Management Research, 2025)
Dark tourism, an emerging niche in India’s travel landscape, offers a unique exploration of sites marked by history’s tragedies and mysteries. This form of tourism invites travelers to engage with the stories of resilience, loss, and humanity’s complex relationship with mortality. From the haunting silence of Jallianwala Bagh to the ghostly allure of Bhangarh Fort, these destinations challenge visitors to reflect on the past and its enduring impact on identity and culture. India’s vast and diverse history makes it a fertile ground for this growing segment, providing not only emotional and educational experiences but also opportunities to preserve heritage and foster deeper connections with history. Despite its potential, dark tourism raises critical ethical, sustainability, and social considerations. Questions about respecting the memories of those affected, balancing commercialization with authenticity, and the equitable distribution of economic benefits remain significant challenges. By addressing these concerns, dark tourism can evolve into a meaningful form of travel that honors the lessons of the past while enriching the travel experience. As India’s tourism industry continues to expand, integrating dark tourism thoughtfully can diversify offerings and contribute to a more holistic understanding of the nation’s multifaceted history.